Novos rumos para o telejornalismo: a abordagem da notícia na Segunda Tela do Jornal da Cultura - Silva, Elane Gomes da (2014)
The Internet and its resources have changed the way people watch TV. The experience is marked by changes in the concepts, standards and practices for television and, therefore, the genres are like magazines. New ways of thinking about television information will become part of everyday life. Mobile connections more easily allow the public the opportunity to enjoy interactive format, which manages the exchange of ideas and debate in groups of people. Find a scenario that portable communication devices (smartphones, tablets and computers) when connected to the Internet can serve as a second screen (SS) for complementation of a content stream TV broadcasting. Thus, viewers receive television content through a newscast that keeps conventional formats (such as presentation and report), but presents them in different platforms using the specific language of each half, as the resources available to allow additional Information. This relieves the user to disperse the core material and keep submerged in the news. In this thesis, the experience of using Second Screen in the Journal of Culture is analyzed, the national broadcaster associated with the Padre Anchieta (TV Cultura) Foundation. That newscast was chosen by reason of being a Brazilian news pioneer in the practice of the second screen. The experiment was active for six months. To understand the uses, how it was organized and launched the SS Jornal da Cultura turned to case study and techniques, such as interviews. We use some observations newsmaking (theory of Journalism). These methodological contributions have given the necessary support for research, highlighting a series of questions roadmap, implementation of direct observations, collecting data and finally analyzing them. He obtained important results for the basis for further research on the topic. Understanding as adopted by the news, question the editing of the material is not available on second screen, the sources, and still found the need to organize more meshed team, which is comprised of journalists and media professionals. We intend our results suggest parameters for this type of television journalism, appeared on the changes brought about by the advance of technology, addressing concepts such as convergence, interactivity, immersion, and mobile TV experience.